Oxidative Formation of Disulfide Bonds by a Chemiluminescent 1,2-Dioxetane under Mild Conditions - Sauer, Caroline; Köckenberger, Johannes; Heinrich, Markus (Journal of Organic Chemistry, 2020)
The oxidation of alkyl thiols to disulfides has been achieved under mild conditions using a chemiluminescent 1,2-dioxetane as a stoichiometric oxidant. Besides the mild and biocompatible reaction conditions, this approach offers the possibility to monitor the presence of thiols through oxidation and chemiluminescence of the remaining dioxetane.
CRIS-Team WoS Importer:2020-08-07